Satisfying human needs at low material footprints: An investigation on the role of provisioning systems - Félix Garnier (Post-growth Economics Network (PEN), 2025)
To achieve social and environmental sustainability, humankind must balance satisfying human needs and preventing ecological collapse. The material footprint-the total materials required for production and consumption-plays a crucial role in this dynamic. This study uses data from 151 countries and a regression-based moderation approach to analyse how material footprints and human need satisfaction are influenced by socio-economic factors known as "provisioning factors."Countries with strong socioecological performance were characterized by factors such as democracy, rule of law, public health coverage, effective corruption control, access to electricity and clean fuels, trade and transport infrastructure, and urbanization. In contrast, weaker socio-ecological performance was often marked by extractivism and inequality. Improving provisioning systems could help countries reduce material use while enhancing need satisfaction. Yet, even under favorable conditions, the current economic system remains incompatible with socio-ecological sustainability, highlighting the need for more radical changes to meet human needs with minimal material consumption.
Keywords: C51; C53; Q56; Q57; 330; material footprint; human needs; provisioning systems; sustainability